AUTOMATION OF PRODUCTION PROCESSES IN THE CONDITIONS OF INFORMATIZATION AND DIGITALIZATION OF THE ECONOMY OF THE REPUBLIC OF UZBEKISTAN - L. A. Kadyrova; N. V. Argunova (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses and analyzes possible methods and the degree of automation of production in the conditions of informatization and digitalization of the Republic of Uzbekistan. The article analyzes the legislative base of the state aimed at strengthening the process of informatization and digitalization of all spheres of the economy. The concepts of local, complex, and full automation are introduced. Examples of automated control systems of real sectors of the economy are considered.